Effects of dexmedetomidine on oxidative stress, programmed cell death, liver function, and expression of peripheral immune cells in patients with primary liver cancer undergoing hepatectomy - Li, WenYing; Chen, MingHao; Gong, YuXin; Lin, Feng; Sun, Chen (Frontiers in Physiology, 2023)
Study background: Primary liver cancer is a severe health issue implicating health burden to many people across the globe. Oxidation and the subsequent cell death impairs liver function and provokes immune response. The present article investigates the effect of dexmedetomidine on oxidation, cell death, the expression of peripheral immune cells, alongside liver function. The clinical data will represent the facts and evidence of the effects of this intervention. Materials and methods: We analyzed clinical data reporting various accounts of the effects of dexmedetomidine on oxidation, cell death, the expression of peripheral immune cells and liver function among patients who underwent hepatectomy. The surgical procedure reported the differences in cell death as procedural outcomes among pre- and post-treatment records were compared and contrasted. We found decreased cell apoptosis in the treatment group: the number of incisions to remove dead cells were lower in the treatment group than the pre-treatment group. Likewise, low oxidation was reported in pre-treatment records than the post-treatment records. The expression of peripheral immune cells was higher in the pre-treatment clinical data than post-treatment, suggesting a reduction in oxidation following dexmedetomidine treatment. Liver function was a function of oxidation and cell death outcomes. In the pre-treatment clinical data, liver function was poor, whereas improved functions were reported in the post-treatment clinical data. Results and discussion: We found compelling evidence of dexmedetomidine’s effects on oxidative stress and programed cell death. The intervention suppresses the production of reactive oxygen species and the consequential apoptosis. Additionally, liver functions improve due to the decrease in hepatocyte apoptosis. Since the peripheral immune cells are expressed against tumors, a decrease in the progression of primary liver cancer decreased the expression of the peripheral immune cells. Conclusion: Dexmedetomidine’s positive effects stood out in the present research article. The intervention reduced oxidation by balancing the production of the reactive oxygen species and the detoxification processes. Reduced oxidation implicated reduced cell death through apoptosis, which resulted in low expression of peripheral immune cells and improved liver functions.